Identification of new drug-like compounds from millets as Xanthine oxidoreductase inhibitors for treatment of Hyperuricemia: A molecular docking and simulation study. (October 2018) - Pathak, Rajesh Kumar; Gupta, Ayushi; Shukla, Rohit; Baunthiyal, Mamta
Graphical abstract: Highlights: A computational approach to identify natural inhibitors of Xanthine oxidoreductase from Millets. Comparative docking studies of identified millet derived compound(s) with available drugs were performed. Based on RMSD, RMSF, Radius of gyration, PCA, Gibbs free energy and binding free energy values of the simulated protein-ligand complexes, it was concluded that the selected millet derived compounds displayed identical and even better activity than the reference drugs i.e. Febuxostat and Allopurinol. It was analysed that Luteolin possesses more stability with good ADMET properties. Therefore, it is capable to inhibit the overexpression of HsXOR's by regulating uric acid pathway. Abstract: Xanthine oxidoreductase plays an important role in formation of uric acid and its regulation during purine catabolism. Uncontrolled expression of this enzyme is responsible for overproduction and deposition of uric acid in blood that is potentially injurious because it can breakdown DNA and protein molecules, triggering many diseases. Human Xanthine oxidoreductase (HsXOR) is considered to be a pharmacological target for the treatment of hyperuricemia. Many of the HsXOR-inhibitor drugs such as Febuxostat and Allopurinol are known to have significant adverse effects. Therefore, there is an urgent need to develop new HsXOR-inhibitor drugs with less or no toxicity for the long-term treatment or prevention of hyperuricemia-related diseases. Many nutritious and medical functions have been reported in millets. Present work deals with identification of millet derived compounds in terms of their interaction with target, HsXOR through molecular docking and dynamic simulation studies. Of thirty two chosen compounds, Luteolin and Quercitin showed more binding affinity with HsXOR than reference drugs, Febuxostat and Allopurinol. Molecular dynamics simulations (20 ns long) revealed that Luteolin-protein complex was energetically more stable than Quercitin-protein complex. The millet derived compounds i.e. Luteolin and Quercitin showed binding energy −9.7 kcal/mol whereas the known drugs i.e. Febuxostat and Allopurinol showed binding energy −8.0 kcal/mol and −5.5 kcal/mol respectively. Based on the study, Luteolin possess high potential to be considered for trial as an inhibitor of HsXOR as it may regulate the pathway by inhibiting HsXOR. Further investigations are proposed to consider Luteolin for developing future drugs from millets and other natural sources.